Gustatory images of Myroslav Yaremak (based on the materials of performances) - Бабій, Надія (Taras Shevchenko National University of Kyiv, 2023)
The article constitutes a segment of the author's research on the representation of social practices through artistic production processes in twenty-first-century Ivano-Frankivsk. It delves into the issue of intercultural communication by examining gustatory themes within the performances of the action artist, Myroslav Yaremak. The study concentrates on actions that revolve around artistic depictions of food and beverages' growth, processing, and consumption, recontextualized within the present culture and politics of a provincial city amidst a globalized backdrop. Furthermore, the article explores the documentation aspects and the societal impact of the performances «Alma mater», «Sower», and «In vino veritas» on the small-town community. The material is organized thematically, revealing content categories such as milk, grain (seeds), and wine as significant markers. The structure of the work revolves around life experiences, meanings, and artistic images. The methodology encompasses semiotic studies by Roland Barthes, performance studies popularised by Richard Schechner, and food studies exemplified in the works of Crystal Neely. It analyses how the chosen categories' meaning and significance, as well as the artist's associated actions, evolve due to changing political or cultural circumstances. The primary empirical foundation of this study comprises self-archived performance artefacts, photo documentation sourced from Ivano-Frankivsk photographers' archives of the 1990s and 2010s, self-descriptions, performance documentation, and interviews with Myroslav Yaremak conducted between 2022 and 2023. The article reveals the process of transforming specific gestural acts into universal ones through ingrained images within daily experiences. It demonstrates how the form of performance and reperformance was shaped by cultural or political history, interpreted through the subjective experiences of the artist and his assistants. Consequently, it portrays gestural acts in the work as mediums of social interaction, wherein recipients (assistants and spectators) become active participants within the artwork.

Стаття є одним із аспектів авторського дослідження питань репрезентації соціальних практик через процеси мистецького виробництва Івано-Франківська у ХХІ столітті. Виокремлена проблема міжкультурної комунікації крізь призму аналізу густативної тематики у перформансах художника-акціоніста Мирослава Яремака. У фокусі дослідження акції, пов’язані з художніми моделями процесів вирощування, переробки і споживання їжі та напоїв, переосмислені відповідно до контексту актуальної культури та політики провінційного міста на тлі глобалізованого світу. Додатково розглянуті питання документації та впливу на містечковий соціум перформансів «Alma mater», «Сіяч», «In vino veritas». Систематизація матеріалу виконана за тематичним принципом, що дозволив виділити в якості проблемних маркерів молоко, зерно (насіння), вино. Структура роботи формується навколо категорій життєвого досвіду, смислу, художнього образу. Застосовані культурсеміотичний підхід Ролана Барта, методології performance studies Річарда Шехнера та food studies Крістала Неллі. У статті аналізується, як змінюються зміст і значення обраного маркера та оголошених митцем дій внаслідок нових політичних чи культурних обставин. Головною емпіричною базою дослідження стали самоархівовані артефакти перформансів, фотодокументація, виявлена у архівах івано-франківських фотохудожників 1990-х та 2010-х років,самоописи та документація перформансів, інтерв’ю із Мирославом Яремаком, зібрані у 2022–2023-му роках. Розкрито процес перетворення конкретних густативних актів в універсальні через стійкі образи, закріплені у буденному досвіді. Доведено, що форма перформанса та реперформанса кожного разу визначалась культурною чи політичною історією, інтерпретованою через суб’єктивний досвід митця та його асистентів. Таким чином густативний акт у роботі представлений як середовище соціальної взаємодії, а реципієнти (асистенти і глядачі) – активними учасники мистецького твору.
Густативні образи Мирослава Яремака (на матеріалах перформансів)
Keywords: gustatory image; identity; performance; Myroslav Yaremak; густативний образ; ідентичність; перформанс; Мирослав Яремак